Pengaruh Pengawasan Dan Pelayanan Fasilitas Baggage Handling System (BHS) Terhadap Tingkat Kepuasan Penumpang Garuda Airline Di Terminal 3 Bandara Soekarno-Hatta - Achep Satria Permana; Dwi Agustina (Jurnal Ilmu Administrasi Publik, 2022)
This study aims to identify the impact of service quality on passengers’ satisfaction at Terminal 3 of Soekarno-Hatta Airport. Particularly, this study included a question on how the supervision and service of the Baggage Handling System (BHS) affects the satisfaction of Garuda Indonesia Airlines passengers at Terminal 3 of Soekarno-Hatta Airport. This study applied a survey using a questionnaire started from 12 February 2021 at 07:59:35 p.m. to 20 February 2021 at 10:41:52 p.m., which collected part of the whole data. In addition, this study employed a quantitative associative method. The survey involved 404 Garuda Indonesia passengers at Terminal 3 as the samples. The data were collected through observation and questionnaires distribution. This survey applied a non-stochastic sampling method with an intentional sampling method. In this study, we analyzed the data using simple linear regression. Based on the scores obtained from the survey results, there was a significant impact of the supervision and service of Baggage Handling System (BHS) on the satisfaction of Garuda Airline passengers at Terminal 3 of Soekarno-Hatta Airport, with a correlation coefficient of 0.764 and an error rate of 5%. This result indicated that the operational status of passengers’ satisfaction on BHS remained relevant with passengers’ expectations, and passengers’ satisfaction on BHS operation at Terminal 3 has fulfilled their current needs. In conclusion, the impact level of supervision and service of the Baggage Handling System (BHS) on passengers’ satisfaction amounted to 96.5%, while the rest, 3.5%, was influenced by other factors.